The Maritime Dimension of Sustainable Energy Security - Narula, Kapil (Singapore : Springer Singapore : Imprint: Springer, 2019)
The maritime domain and sustainable energy are two critical aspects of the twenty first century which will shape the future of humanity. Although the maritime domain is inextricably interlinked with Sustainable Energy Security (SES), many aspects are discussed in isolated silos. This book aims to fill in this gap by presenting a holistic view of the maritime dimension of SES. It includes various topics such as the global energy system, energy supply chains, energy trade, shipping of energy commodities, energy markets, protection of maritime energy supply lines and the role of military in providing maritime security. It also focuses on harnessing offshore energy resources, both hydrocarbons and marine renewable energy and discusses the developments in lowering emissions from the shipping sector. The book is written for the general reader as well as students who are undergoing a course in energy systems, maritime management, naval studies and energy sustainability. The content is tailored to meet the intellectual curiosity of the inquisitive reader and introduces various specialized topics which are dealt in a simple and concise manner. It is hoped that this book would bridge the gap in the understanding of the maritime dimension of SES.
Introduction to Sustainable Energy Security -- The need for Sustainable Energy Security -- Energy transportation in a dynamic maritime environment -- Shipping and Port Infrastructure -- Maritime Security Challenges -- Offshore Energy Resources and Emerging Opportunities -- Energy Transportation and Shipping Emissions -- Policy Options and Strategies -- Conclusion and Recommendations.
Description based on publisher-supplied MARC data.
Keywords: Energy and state; Energy policy; Energy security; Ocean engineering; Shipping; Transportation; Offshore Engineering; Energy Policy, Economics and Management; Energy Policy, Economics and Management; Energy Security; Maritime Economics; Transportation